AVALIAÇÃO MORFOLÓGICA DE FRUTOS DE CASTELA TWEEDIEI PLANCH. (SIMAROUBACEAE), TRICHILIA CATIGUA A. JUSS. (MELIACEAE), LUEHEA DIVARICATA MART. ET ZUCC. (MALVACEAE) - Franco, Elci T. H.; Afonso, Marcelo V.; Saturno, Camila (Salão do Conhecimento, 2013)
Resumo